Pengentasan buta aksara berbasis pendekatan “semua anak cerdas” untuk guru SD - Awal Nur Kholifatur Rosyidah; Lalu Hamdian Affandi; Muhammad Erfan; Itsna Oktaviyanti; Mohammad Archi Maulyda; Iwan Hamdani (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
This service activity aims to improve the literacy and numeracy skills of elementary school (SD) children in Karang Sidemen Village, North Batukliang District, Central Lombok Regency through the "All Smart Children" Program which trains teachers regarding the urgency of learning basic literacy and numeracy for children. , and how to teach basic literacy and numeracy using the TaRL (Teaching at the Right Level) method. The activity is carried out in stages, namely 1) Coordination meeting, 2) Simulation of material presentation, 3) Preparation of activity logistics, 4) Implementation of workshop activities consisting of 2 waves, and 5) Evaluation of success indicators seen from the increase in scores on pretest-posttest which are grouped into 4 levels. There are differences in the characteristics of low-grade teachers and high-grade teachers during the training activities. Based on the results of the pretest and posttest, it is known that there are 24 out of 31 participants who experienced an increase in level. Workshop activities can be considered quite successful with the percentage of success of training activities in general is 77.41%.